The Tale of Genji : translation, canonization, and world literature - Emmerich, Michael (Columbia University Press, 2013)
"Ambitious and engrossing, this volume thoroughly revises the conventional narrative of The Tale of Genji's early modern and modern history, arguing that until the 1930s readers were less familiar with the eleventh-century work than scholars have assumed. Exploring iterations of the work from the 1830s to the 1950s, Michael Emmerich demonstrates how translations and the global circulation of discourse they inspired turned The Tale of Genji into a widely read classic, reframing not only our understanding of its significance and influence but also the processes that have canonized the text. In doing so, he supplants the passive concept of 'reception' with the active notion of 'replacement, ' revitalizing the work of literary criticism"--Provided by publisher.